The role of fire in the mid-Holocene arrival and expansion of lodgepole pine (Pinus contorta var. latifolia Engelm. ex S. Watson) in Yukon, Canada. (January 2015) - Edwards, Mary; Franklin-Smith, Leanne; Clarke, Charlotte; Baker, Joanna; Hill, Sian; Gallagher, Katherine
In north-west Canada, Pinus contorta (lodgepole pine) has been migrating northwards and westwards for millennia. Its regeneration is currently enhanced by fire, which may act as a trigger for local population expansion. Using Holocene charcoal records from four small (<10 ha) lakes in southern Yukon, we investigated the relationship between long-term Pinus population dynamics and fire. Fossil stomata extracted from dated lake sediments indicate pine was present at low densities in southern Yukon forests by 6000 cal. yr BP. At each site, the main population expansion (indicated by an increase in Pinus pollen from <5% to values as high as 60%) occurred 2000–>4000 years after the first local appearance of Pinus, suggesting a long period of stasis at low densities. Population increases – based on pollen accumulation rates (PARs) – occurred at different times at the four sites. Estimated expansion periods were 2500–800 years, and population doubling times were 150–600 years, similar to previous estimates. Estimated fire return intervals (FRIs) fluctuated over time. At all sites, the Pinus expansion began during a phase with a relatively short FRI, but only one difference between the mean FRIs before and during the Pinus rise was statistically distinguishable. Nor was the subsequent higher abundance of pine associated with shorter FRIs. It is unlikely that regional pine expansion is primarily linked to changes in climate or a climate-mediated fire regime, although expansion may have been triggered at individual sites during a period of high fire frequency. The long period of stasis at low population densities suggests intrinsic control of population growth; possibly Pinus expansion was initially constrained by lowered reproductive fitness (Allee effect) and/or interaction with local site-based factors.